Analisis Jejaring Sosial Smartfren Pada Sosial Media Twitter Dengan Metode Text Network Analysis (TNA) - Tyas, Delia Hayyuning; Suganda, Grishelda Amelia; Putri, Hanifah Hindra; Nurtikasary, Meyke; A.R, Sakina Ulfa (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The study aims to determine and analyze the responses of consumers who have used smartfren through comments on social media twitter regarding the network, price, and quality of smartfren in Indonesia. Useful to find out what consumer complaints are often submitted by smartfren users. With smartfren's superior services, smartfren 4G LTE advanced, VoLTE to enable customers to enjoy calls with HD quality, international services, smart world, smart U, and super4G smartfren. Smartfren also provides unlimited services 24 hours a month. With this Text Network Analysis method, the author wants to find out whether there are negative comments about this smartfren service so that the company will finally be able to find out what problems often arise and can be fixed so that they can make the company even better.